Doktrína řádného procesu jako prostředek inkorporace Bill of Rights - Jaroslav Ženíšek (Právněhistorické studie)
The incorporation of the Bill of Rights against the states through the Fourteenth Amendment belongs among the most complex topics of American constitutional law. The first question to ask is obviously “Was the Bill of Rights incorporated against the states with the ratification of the Fourteenth Amendment?” Even if we answer this essential and difficult question in the affirmative, we face another one, no less important, which is: Through which of the clauses of section one of the Fourteenth Amendment was incorporation implemented? Among the proponents of the incorporation theory we find two groups: one that advocates incorporation through the privileges or immunities clause and another one that supports incorporation through the due process clause or the so called doctrine of substantive due process. Substantive due process is one of the phenomenons of American constitutional law that influenced legal evolution in the United States in a fundamental way, mainly during the 20th century when the concept of substantive due process experienced a steep rise that manifested itself not only in the area of protection of rights and freedoms not explicitly mentioned in the Constitution, but also those clearly mentioned in the amendments that constitute the Bill of Rights. It was the very substantive due process doctrine which was used by the federal Supreme Court as basis for gradual incorporation of the individual guarantees contained in the Bill of Rights to state and local level. It is, however, necessary to ask whether the Supreme Court, while trying to reach this goal, did not embrace a doctrine which lacks basis in the text of the Constitution and the traditions of the common law, thus being only an artificial creation of the Supreme Court itself as to this day, many suggest. This paper deals with the origins, historical meaning and evolution of the concept of due process and tries to show whether the substantive due process doctrine has a real legal foundation and can therefore serve as means for incorporation of the Bill of Rights.